Uji Aktivitas Antibakteri Ekstrak Etanol 96% Daun Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) terhadap Bakteri Staphylococcus epidermidis - Andriyani; Fransisca Jesica Putri Santoso; Febbyasi Megawaty Rangka (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Acne is a skin problem that occurs due to inflammation of the polysebaceous follicles. One of the bacterial causes of acne infection is Staphylococcus epidermidis, which is found on human skin and mucous membranes. Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) is a native plant from Papua, Indonesia. Mahkota dewa leaves contain active compounds, including alkaloids, saponins, and tannins, which function as antibacterials. The objective of this research was to determine the antibacterial activity of 96% ethanol extract of Mahkota Dewa leaves against Staphylococcus epidermidis bacteria using the disc diffusion method and to determine the Minimum Inhibitory Concentration (MIC) using a UV-Vis spectrophotometer. The extract yielded 23.285% and contained secondary metabolite compounds, including alkaloids, flavonoids, tannins, saponins, phenols, steroids, and quinones. The results of the antibacterial activities were 8.98 mm, 10.24 mm, and 13.14 mm at extract concentrations of 100,000 ppm, 250,000 ppm, and 500,000 ppm, respectively. Concentrations of 100,000 ppm and 250,000 ppm indicate a moderate inhibition zone, while a concentration of 500,000 ppm indicates a strong inhibition zone against the growth of Staphylococcus epidermidis bacteria. The MIC of 96% ethanol extract of Mahkota Dewa leaves was at a concentration of 6,250 ppm with an IR% of 8.314%.